2021
DOI: 10.29021/spdv.79.1.1299
|View full text |Cite
|
Sign up to set email alerts
|

Acute Telogen Effluvium in Patients Recently Infected with SARS-CoV-2

Abstract: Introduction: The hair cycle is especially susceptible to endogenous and exogenous stimuli, including febrile states and emotional stress, which are a constant in this pandemic era. In this case series, we describe the clinical characteristics of patients recently diagnosed with SARS-CoV-2 infection who developed acute telogen effluvium. Material and Methods: We performed a registry of patients with laboratory-confirmed SARS-CoV-2 infection who developed acute telogen effluvium and actively sought medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 19 publications
6
9
0
Order By: Relevance
“…In alignment with our findings, acute TE was also reported during the life‐threatening influenza pandemic of 1918–1919 (commonly known as Spanish flu), with hair loss developing 2–6 weeks after the onset of fever 24,32 . Moreover, we observed that acute TE occurred around a mean duration of 74 days after the onset of COVID‐19 symptoms.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In alignment with our findings, acute TE was also reported during the life‐threatening influenza pandemic of 1918–1919 (commonly known as Spanish flu), with hair loss developing 2–6 weeks after the onset of fever 24,32 . Moreover, we observed that acute TE occurred around a mean duration of 74 days after the onset of COVID‐19 symptoms.…”
Section: Discussionsupporting
confidence: 90%
“…However, the trichoscopic and trichogram findings did not differ from classic acute TE. 25 As shown in our results, the detailed trichoscopic findings reported across the studies most commonly included reduced hair density, 19,24,30 empty hair follicles, 9,24,25,30 short regrowing hair, 24,25 and/or hair in the telogen phase. 16,19 Similar to the findings of classic acute TE, there was a female preponderance (67.5%) in the patients diagnosed with acute TE post-COVID-19.…”
Section: Management and Outcomes Of Acute Tesupporting
confidence: 69%
See 3 more Smart Citations